Spontaneous coronary artery dissection involving the left main stem: assessment by intravascular ultrasound. Issue 7 (14th June 2004) - Auer, J; Punzengruber, C; Berent, R; Weber, T; Lamm, G; Hartl, P; Eber, B
Abstract : This case report describes the devastating consequences of spontaneous coronary dissection in a 36 year old female patient who otherwise had a normal coronary arteriogram. Intravascular ultrasound showed coronary artery dissection and intramural haematoma at the left main stem coronary artery. Acute coronary syndrome developed and subsequently surgical revascularisation was performed successfully.